1998
DOI: 10.1148/radiographics.18.3.9599384
|View full text |Cite
|
Sign up to set email alerts
|

Role of CT angiography in the preoperative evaluation for laparoscopic nephrectomy.

Abstract: Laparoscopic nephrectomy (LN) was recently introduced as a minimally invasive alternative 'From the Departments of Radiology (P.A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 0 publications
2
46
1
1
Order By: Relevance
“…Accurate depiction of the renal vessels is of paramount importance for potential kidney donors, especially on the left, as it is often the preferred side for renal harvesting (13).…”
Section: B Amentioning
confidence: 99%
“…Accurate depiction of the renal vessels is of paramount importance for potential kidney donors, especially on the left, as it is often the preferred side for renal harvesting (13).…”
Section: B Amentioning
confidence: 99%
“…Thus, multi-slice Angio-CT has replaced the conventional arteriography in the evaluation and study of vascular anatomy and diagnosis of vascular diseases of the kidney. Smith et al 15 showed that Angio-CT correctly identified renal arterial anatomy in 41 out of 42 patients undergoing preoperative evaluation for nephrectomies. According to Rubin et al 16 , this method has 100% sensitivity in the identification of renal arteries.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Traditionally, renal angiography and excretory urography have been used to evaluate the anatomy of renal arteries and renal function, respectively, in potential kidney donors. However, several studies have shown that helical computed tomography (CT) angiography can replace renal angiography and excretory urography in the evaluation of potential kidney donors (3)(4)(5)(6)(7)(8)(9). Hence, helical CT angiography has become an accepted method for the evaluation of living donors before they undergo laparoscopic nephrectomy.…”
Section: Introductionmentioning
confidence: 99%